Malocclusion influence on balance and posture: a systematic review. - Stancker, Tatiane Garcia; Silva, Andréia Cristina de Oliveira; Neto, Hugo Pasin; Rodrigues, Cristiane Delgado Alves (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Malocclusion can be defined as an imbalance between the masticatory system and neuromuscular Temporomandibular joint. It is considered as a result of the sum of genetic, environmental and postural elements therefore of multifactorial origin. Objective: To review the existing literature if malocclusion influence in posture and balance of the subject. Methods: This is a systematic review, which searched up clinical studies, published between 2009 and 2014 in English, Portuguese and Spanish, in the databases SciELO, PubMed, Lilacs and Sience Direct, using the keywords malocclusion/posture and malocclusion/body balance. Studies were included that had to evaluate the posture and/or balance in patients with malocclusion, were excluded systematic reviews and studies that did not correspond to the proposed theme. Results: In addition to the articles found in all databases, the corpus generated by the literature consisted of 828 records; 13 of them responded to the proposed theme. About the selected literature, eight studies showed significant results regarding the relationship between malocclusion and posture, and two as malocclusion and body balance. Conclusion: it was concluded that malocclusion is associated with the posture of the changes, since the balance, only two studies presented this outcome and was in a considered positive for the worsening of static equilibrium, but with no clinical application, and another positive for improves dynamic balance.